How accurate are financial reports of british charities? - Canh Thien Dang; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2016)
The demand for transparency and reliability of information from nonprofit organisations has surged as stakeholders increasingly use nonprofit financial information for contracting and regulating decisions. Contrary to previous studies, we theoretically show that attempts to enhance the monitoring of nonprofits through raising governance spending may not always lead to higher quality financial reports. Non-profits with larger charitable spending will be more inclined to report accurately, only if their spending on governance activities exceeds a certain threshold. To test the prediction, we measure the reporting quality at organisational level using public financial data from the UK Third Sector from 2007 to 2015. As popular measures require large and detailed data that are not usually available in the non-profit sector, we use Benford's Law to construct innovative and easy-to-replicate measures of information irregularities. Using these measures, we find robust results to support the theoretical predictions and address potential endogeneity by the conventional IV approach and Lewbel's (2012) heteroscedasticity-based IV estimator. This paper contributes to a heated debate in the UK regarding policies to govern the non-profit sector. We suggest that tighter monitoring might be ineffective to increase the sectoral transparency and accountability.
Keywords: L31; L44; D82; 330; British charities; non-profits; report accuracy; Benford's Law